Reading Between the Lines: Accessing Information via YouTube's Autocaptioning - Smith, Chad E.; Crocker, Samantha; Allman, Tamby (Online Learning, 2017)
This study and discussion center upon the use of YouTube’s automatic captioning feature with college-age adult readers. The study required 75 participants with college experience to view brief middle school science videos with automatic captioning on YouTube and answer comprehension questions based on material presented auditorily and/or through the automatic captions. Participants were divided into groups and presented with the captioned videos with or without sound. The videos, which all focused on the solar system, contained low and high instances of errors within the captions. The research found that comprehension of the automatic caption text varied significantly based on how the participants viewed the videos, with significantly more errors in comprehension for the group that viewed the high error video with automatic captioning only.